A comprehensive analysis of the computed tautomer fractions of the imidazole ring of histidines in Loligo vulgaris - Vorobjev, Yury N. (2017)
A recently introduced electrostatic-based method to determine the pKa values of ionizable residues and fractions of ionized and tautomeric forms of histidine (His) and acid residues in proteins, at a given fixed pH, is applied here to the analysis of a His-rich protein, namely Loligo vulgaris (pdb id 1E1A), a 314-residue all-β protein. The average tautomeric fractions for the imidazole ring of each of the six histidines in the sequence were computed using an approach that includes, but is not limited to, molecular dynamic simulations coupled with calculations of the ionization states for all 94 ionizable residues of protein 1E1A in water at pH 6.5 and 300 K. The electrostatic-calculated tautomeric fractions of the imidazole ring of His were compared with predictions obtained from an existent NMR-based methodology. Our results indicate that: (i) the averaged electrostatic-based tautomeric predictions for the imidazole ring of all histidines of Loligo vulgaris are dominated by the Nε2-H rather than the Nδ1-H form, although such preferences from the NMR-based methodology are not so well defined; (ii) the computed average absolute difference between the electrostatic- and the NMR-based tautomeric predictions among all six histidines vary among 0% to 17%; (iii) for the His showing the largest fraction of the neutral form (81%), the absolute difference between the NMR- and electrostatic-based computed tautomeric predictions is only 3%; and (iv) the tautomeric predictions for the imidazole ring of His computed with the NMR-based methodology are stable within a certain, well-defined, range of variations of a tautomer-related parameter.